Advanced technology-driven therapeutic interventions for prevention of tendon adhesion: design, intrinsic and extrinsic factor considerations - Zhang, Qiang; Yang, Yuhe; Yildirimer, Lara; Xu, Tianpeng; Zhao, Xin (Acta biomaterialia, 2021)
Tendon adhesion formation describes the development of fibrotic tissue between the tendon and its surrounding tissues, which commonly occurs as a reaction to injury or surgery. Its impact on function and quality of life varies from negligible to severely disabling, depending on the affected area and extent of adhesion formed. Thus far, treatment options remain limited with prophylactic anti-inflammatory medications and revision surgeries constituting the only tools within the doctors’ armamentarium - neither of which provides reliable outcomes. In this review, the authors aim to collate the current understanding of the pathophysiological mechanisms underlying tendon adhesion formation, highlighting the significant role ascribed to the inflammatory cascade in accelerating adhesion formation. The bulk of this article will then be dedicated to critically appraising different therapeutic structures like nanoparticles, hydrogels and fibrous membranes fabricated by various cutting-edge technologies for adhesion formation prophylaxis. Emphasis will be placed on the role of the fibrous membranes, their ability to act as drug delivery vehicles as well as the combination with other therapeutic structures (e.g., hydrogel or nanoparticles) or fabrication technologies (e.g., weaving or braiding). Finally, the authors will provide an opinion as to the future direction of the prevention of tendon adhesion formation in view of scaffold structure and function designs.
Gesehen am 05.05.2021